Strengthening Islamic Character through Four Integrated Mechanisms in Primary Teacher Education: A Qualitative Case Study of PGSD Students at UNM Campus V - Lukman, Lukman; Hilaliyah, Nur; Muthmainnah, Muthmainnah; Rahman, Amri; Mujahidah, Mujahidah; Khaerunnisa, Khaerunnisa (Jurnal Pendidikan Islam, 2024)
Purpose – This study examines how Islamic values are internalised and sustained among Primary School Teacher Education (PGSD) students at a regional Indonesian campus, addressing the gap between moral knowing and moral action and the conditions that stabilise practice. Design/methods/approach – A qualitative case study was conducted at   (Universitas Negeri Makassar) Campus V, Parepare using purposive sampling: 30 PGSD students, one Islamic Religious Education (PAI) lecturer, three lecturers involved in character initiatives, and two da’wah-organisation administrators. Data comprised participant observation, semi-structured interviews, and document analysis. Analysis followed Miles–Huberman procedures; trustworthiness was enhanced through triangulation, member checking, and peer debriefing. Ethical clearance was obtained. The study was guided by Lickona’s moral knowing–feeling–action and Self-Determination Theory. Findings – Four reinforcing mechanisms structure a pathway from knowledge to practice: (i) PAI pedagogy; (ii) campus religious activities; (iii) worship journaling; and (iv) lecturer exemplarity supported by facilities/culture. Internalised values include faith–piety, honesty–trustworthiness, a clarified distinction between discipline (temporal order) and istiqamah (cross-week steadiness), and tolerance. Enablers comprise intrinsic motivation, family/community continuity, lecturer modelling, and fit-for-purpose facilities; barriers include heterogeneous motivation, academic fatigue, misaligned home rhythms, uneven modelling, scheduling frictions, and digital distraction. Participation was more focused when ≥ 3 mechanisms operated within a week, a pattern recurrent across weeks and settings. Research implications – Recommend a weekly cycle (class stimulus to collective engagement to reflective journaling to exemplarity/ambient cues), protected prayer-time windows, SOPs for lecturer exemplarity, facility optimisation, light peer review of journals, family briefs for commuters, digital-hygiene routines, schedule de-confliction, and recovery-time metrics.